B-Model approaches to instanton counting - Krefl, Daniel; Walcher, Johannes (Arxiv, 2014)
This is the 13th article in the collection of reviews "Exact results in N=2 supersymmetric gauge theories", ed. J. Teschner. It discusses the relation between the instanton partition functions and the partition function of the topological string from the perspective of the B-model. The instanton partition functions provide solutions to the holomorphic anomaly equations characterising the partition functions of the topological string.